Use of a Handheld Thermal Torch as a Herbicide-Resistance Management Tool - J. Hoyle; J. Reeves; E. Alderman (Kansas Agricultural Experiment Station Research Reports, 2015)
Handheld thermal torches could possibly become a tool to reduce glyphosate-resistant annual bluegrass populations. One month after treatment, 5- and 6-second handheld thermal heat treatments reduced annual bluegrass populations by 50 and 60%, respectively.
Keywords: turfgrass; thermal torch; herbicide-resistance management; annual bluegrass; Poa annua; glyphosate; glyphosate resistance